Strategies to increase community participation in controlling dengue mosquito breeding sites: a scoping review - Rizka Nur Isnaeni; Syamsulhuda Budi Musthofa; Ratih Indraswari (Universitas Gadjah Mada, 2025)
Purpose: Dengue Hemorrhagic Fever (DHF) is a growing global public health problem, particularly in low- and middle-income countries, and is influenced by social, environmental, and behavioral factors. Community participation plays a crucial role in the success and sustainability of dengue prevention. However, limited governance, weak cross-sectoral coordination, the dominance of top-down approaches, and a lack of resource support often hinder optimal community involvement. This study aims to identify literature on strategies to increase community participa- tion in dengue prevention practices. Methods: This scoping review used the methodological framework by Arksey and O'Malley. A scoping review was conducted by searching the Scopus, PubMed, and ScienceDirect databases using keywords related to community participation, prevention, and dengue fever. Original English-language research articles published between 2015 and 2025 and relevant to community-based dengue prevention were selected using the PRISMA process. Results: Eight articles met the inclusion criteria. The review results indicate that strong multi- sectoral governance, a bottom-up, participatory approach, and the use of social capital and local leadership are key to effective dengue prevention. Health education through schools, youth engagement, incentives, and innovative, contextualized interventions contribute to increasing the sus- tainability of prevention practices. Conclusion: Dengue fever prevention requires an integrated approach that positions the community as the pri- mary partner, supported by cross-sectoral collaboration, strengthening social capital, and sustainable resource support so that the impact of pre- vention can be sustained in the long term.